Jassim M. Jawad Bochner curvature tensor of Almost Kahler manifold - Jawad, Jassim (University of Thi-Qar Journal of Science, 2019)
In this paper we study the Bochner curvature tensor of almost Kahler manifold. We found the components of Bochner tensor of almost Kahler manifold in the adjoint G-structure space by using Kirichenko’s tensors. It has been proved that an almost Kahler manifold is a manifold of class if and only if it is Kahler.